Preliminary Clinical Outcomes Following Biologic Augmentation of Arthroscopic Rotator Cuff Repair Using Subacromial Bursa, Concentrated Bone Marrow Aspirate, and Platelet-Rich Plasma - Lukas N. Muench, M.D; Cameron Kia, M.D; Daniel P. Berthold, M.D; Colin Uyeki; Alexander Otto, M.D; Mark P. Cote, D.P.T., M.S; Mary Beth McCarthy, B.S; Knut Beitzel, M.D; Robert A. Arciero, M.D; Augustus D. Mazzocca, M.S., M.D (Elsevier, 2020)
Purpose: To evaluate the clinical outcomes of patients who underwent arthroscopic rotator cuff repair augmented using subacromial bursa, concentrated bone marrow aspirate (cBMA), and platelet-rich plasma. Methods: Sixteen patients were included in the study who underwent arthroscopic rotator cuff repair augmented using subacromial bursa, cBMA, and platelet-rich plasma from January 2018 to July 2018 and had a minimum 1-year follow-up. American Shoulder and Elbow Surgeons (ASES), Simple Shoulder Test, Constant-Murley, and Single Assessment Numerical Evaluation (SANE) scores were collected preoperatively and at terminal follow-up. To determine the clinical relevance of ASES scores, the minimal clinically important difference, substantial clinical benefit, and the patient acceptable symptomatic state thresholds were used. In vitro cellular proliferation of subacromial bursa (nucleated cells/gram) and cBMA (nucleated cells and colony-forming units/cc) samples was evaluated and correlated to clinical outcomes scores. Results: Mean follow-up was 12.6 ± 1.8 months (range 12-19 months). Patients achieved significant improvement in ASES (45.8±22.5pre vs 88.5 ± 14.6post, Δ44.7 ± 20.7; P = .001), Simple Shoulder Test (4.3 ± 3.2pre vs 10.4 ± 1.6post, Δ5.7 ± 3.9, P = .002), Constant-Murley (44.3 ± 18.2pre vs 83.6 ± 17.5post, Δ37.2 ± 21.8; P = .001), SANE (13.3 ± 10.7pre vs 86.3 ± 17.5post, Δ71.9 ± 22.9; P = .001), and pain scores (5.0±2.8pre vs 1.1 ± 1.6post, Δ3.5±2.5, P = .001) at final follow-up. With regards to ASES score, 93.8% of patients achieved the minimal clinically important difference, 93.8% the substantial clinical benefit, and 62.5% reached or exceeded the patient acceptable symptomatic state criteria. There was a significant positive correlation of nucleated cell count of cBMA with postoperative SANE score (r = 0.707; P = .015) and delta in ASES score (r = 0.727; P = .011). All other correlations were found to be nonsignificant (P > .05, respectively). Conclusions: Patients undergoing arthroscopic rotator cuff repair augmented using the Mega-Clot with bursa technique achieved significant improvement in functional outcomes at a minimum 1-year follow-up, with 93.8% of patients reaching substantial clinical benefit. Level of Evidence: Level IV, therapeutic case series.